Answer:
a. F(r) = 12ar^-13 - 6br-7
b. U(r) = -b²/4a.
c. b²/4a
d. a = 6.67E-138J, b = 6.41E-78J
Step-by-step explanation:
Given
U(r) = a/r^12 - b/r^6
a. Calculating Force, F(r)
F(r) = -dU/dr
dU/dr = ar^-12 - br^-6
dU/dr = -12ar^-13 + 6br-7
F(r) = -dU/dr
F(r) = 12ar^-13 - 6br-7
b. Finding the equilibrium distance;
Summation F = 0
First, we solve for r
F(r) = 12ar^-13 - 6br-7= 0
12ar^-13 = 6br-7 --- Multiply both sides by r^7
12ar^-6 = 6b
r^-6 = 12a/6b
r^-6 = 2a/b
r = (2a/b)^-(1/6).......
U(r) = a/r^12 - b/r^6
U(r) = a/((b/2a)^-(1/6))^12 - a/((b/2a)^-(1/6))^6
U(r) = a/(2a/b)² - b/(2a/b)
U(r) = a/4a²/b² - b/2a/b
U(r = ab²/4a² - b²/2a
U(r) = b²/4a - b²/2a
U(r) = (b²- 2b²)/4a
U(r) = -b²/4a.
c.
At Equilibrium distance, (r) = 1.13 * 10^-10
(2a/b)^-(1/6) = 1.13 * 10^-10
(2a/b) = (1.13 * 10^-10)^6
2a = ((1.13 * 10^-10)^6)b
a = ½((1.13 * 10^-10)^6)b
d. Dissociation Energy
b²/4a = 1.54 * 10^-18
b²/4(½((1.13 * 10^-10)^6)b) = 1.54 * 10^-18
b = 1.54 * 10^-18 * 2((1.13 * 10^-10)^6))
b = 6.41E-78J
Solving for a
a = ½((1.13 * 10^-10)^6) * 6.41E-78J
a = 6.67E-138J